HUMAN RESOURCE CAPACITY IN STRENGTHENING VILLAGE FUND GOVERNANCE AT THE GRASSROOTS LEVEL IN BONE BOLANGO DISTRICT, GORONTALO PROVINCE - Haeranah; AYU WIDOWATI JOHANNES; Taufan Alwany; irfan Setiawan (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2025)
Village Fund management in Bone Bolango Regency faces specific challenges related to the readiness of village officials to manage digital-based financial systems. Several reports from the Regency Government since 2022 indicate that villages remain highly dependent on technical assistance. This situation emphasizes the importance of research on village official capacity and digital readiness as key factors in the effectiveness of Village Fund governance in the region. This study aims to analyze in-depth the relationship between village official human resource capacity, digital readiness, and the quality of Village Fund governance in Bone Bolango Regency, Gorontalo Province. This study used a qualitative descriptive approach through in-depth interviews with 27 village officials, participant observation, and analysis of village financial documents and digital application implementation. The results showed that although 19 of the 27 officials had at least a high school/vocational high school education and 6 had a bachelor's degree, only 11 reported being able to operate the village financial application without assistance. Limited digital literacy was evident in delayed data input and errors in uploading accountability documents. Furthermore, 14 of the 19 villages observed experienced internet infrastructure constraints, which frequently delayed the budget verification and disbursement process. These findings indicate that the formal capacity of government officials does not always align with the technical competencies required for digital-based village financial governance. The practical implications of this study emphasize the need for capacity-building programs that focus more on digital literacy, ongoing technical assistance, and improvements to network infrastructure at the village level. Strengthening these aspects has the potential to increase accountability and accelerate the administrative process of Village Fund management in Bone Bolango Regency.